Development of PhytovesiclesCcontaining Triterpenoids from Samadera Indica, - Vidya Viswanad; Subin Mary Zachariah; Aiswarya Sathi; N. A. Aleykutty (Pharmacognosy Research, 2015)
Introduction: Samadera indica belonging to Simaroubaceae family is being used traditionally for many diseases including arthritis, edema, itching, skin diseases, constipation, and general debility. Objective: The effectiveness of any drug delivery system depends upon its ability to deliver the active components at therapeutic level. In this study, a novel phyto vesicular formulation for the enhanced topical delivery of methanol extract of S. indica in order to treat skin infections was developed. Materials and Methods: The methanol extract fraction of leaves of S. indica which showed more antifungal activity was purified to separate an antifungal compound. Phytovesicles were formulated using the more antifungal fraction in order to treat topical and deep seated fungal infections. Pytovesicles were prepared using 1:2 molar ratio of antifungal triterpenoid from S. indica (AFTSI)-phosphatidylcholine by film hydration method. Results and Discussion: Chloroform 100% fraction of methanol extract of S. indica showed more activity against the fungus Candida albicans. Further purification gave a fraction with minimum inhibitory concentration value of 15.6 μg/ml against C. albicans and showed positive test for triterpenoids. The fraction was named as AFTSI. A compound (20 mg) was isolated from this fraction at an RF value. The phytovesicle gel formulated using AFTSI showed enhanced skin permeability and antifungal activity. Conclusion: The study demonstrated that the phytovesicular gel developed using methanol extract of S. indica would be beneficial for treating deep seated fungal infections
Keywords: Phytovesicular gel; Samadera Indica; Triterpenoids